2006
DOI: 10.1186/bcr1604
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of the epithelial-specific transcriptome of normal and malignant human breast cells based on MPSS and array expression data

Abstract: Introduction Diverse microarray and sequencing technologies have been widely used to characterise the molecular changes in malignant epithelial cells in breast cancers. Such gene expression studies to identify markers and targets in tumour cells are, however, compromised by the cellular heterogeneity of solid breast tumours and by the lack of appropriate counterparts representing normal breast epithelial cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
125
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(140 citation statements)
references
References 52 publications
13
125
2
Order By: Relevance
“…First, how do our results compare to existing expression data from human breast tissue? Most existing breast tissue expression signatures were derived to predict tumor subtype 29,30 or disease outcome, [31][32][33][34][35] or to distinguish luminal from myoepithelial cells in RM tissue, 28,36 as opposed to distinguishing between patients with and without breast cancer, and so are not directly comparable to our data. It is therefore not surprising that few of the genes that we find to vary between CN and RM epithelium have been useful in predicting tumor subtype, disease outcome, or epithelial cell type (analyses not shown).…”
Section: Discussioncontrasting
confidence: 51%
See 2 more Smart Citations
“…First, how do our results compare to existing expression data from human breast tissue? Most existing breast tissue expression signatures were derived to predict tumor subtype 29,30 or disease outcome, [31][32][33][34][35] or to distinguish luminal from myoepithelial cells in RM tissue, 28,36 as opposed to distinguishing between patients with and without breast cancer, and so are not directly comparable to our data. It is therefore not surprising that few of the genes that we find to vary between CN and RM epithelium have been useful in predicting tumor subtype, disease outcome, or epithelial cell type (analyses not shown).…”
Section: Discussioncontrasting
confidence: 51%
“…28 We found that 75 of the 105 genes in our list were also differentially expressed between cancer and normal epithelium in that study, and that 80% of these 75 genes showed the same direction of change in both datasets, indicating significant concordance (v 2 test; p 5 0.0002) and demonstrating the similar differential expression of the majority of the 105 genes in an independent data set (see Supplemental File 2).…”
Section: Validation Of Microarray Datamentioning
confidence: 75%
See 1 more Smart Citation
“…Periostin is highly expressed during the earliest stages of bone fracture repair [15] and vascular injury [16] and periostin signaling induces the expression of molecules associated with cutaneous wound repair such as collagen and fibronectin [17,18]. A role in cancer cell metastasis has also been suggested, as periostin is a recognize component of stromal reactions in a variety of tumor types [19][20][21][22][23][24][25][26][27][28][29]. While DD shares some characteristics with each of these repair and disease processes, the role(s) of periostin in this fibromatosis is yet to be determined.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 Some studies have showed that MRPS30 is not expressed in normal breast luminal epithelial cells, but it is upregulated in infiltrating ductal carcinomas. 16 Moreover, it was also a part of a gene expression profile that differentiated ER-positive from ER-negative breast tumors. 11 Interestingly, a SNP rs3761648 in 5' near of MRPS30 is highly correlated with the SNP rs4415084 (r 2 ¼ 0.83 in HapMap CHB, r 2 ¼ 0.72 in HapMap CEU) and located at a site of H3K4Me3 histone modification marks.…”
Section: Discussionmentioning
confidence: 99%